2019
DOI: 10.15689/ap.2019.1803.16248.13
|View full text |Cite
|
Sign up to set email alerts
|

Estimación de la magnitud del efecto en invarianza de medición

Abstract: RESUMENEste trabajo presenta un programa en MS Excel ® para evaluar la magnitud del efecto (ES, por las siglas en inglés) en invarianza de medición de diferentes parámetros como las cargas factoriales, interceptos/thresholds y residuales, con base en estadísticos estandarizados ya conocidos. El funcionamiento del programa y la interpretación de las medidas de ES se ejemplificaron con datos empíricos.Palabras clave: invarianza de medición; magnitud del efecto; programa. RESUMO -Avaliação do tamanho do efeito na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Third, the factorial invariance of the APBS was examined based on gender. The results showed that the APBS measures prosociality in an equivalent way between men and women, with both the variation of indices of fit provided by the general approach [ 104 , 118 , 119 ] and the specific one that measured the effect size of the individual parameter differences [ 120 , 121 , 122 ]. This study considered factor loadings (weak invariance), thresholds (strong invariance), and residuals (strict invariance), which supports hypothesis 3 (H3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the factorial invariance of the APBS was examined based on gender. The results showed that the APBS measures prosociality in an equivalent way between men and women, with both the variation of indices of fit provided by the general approach [ 104 , 118 , 119 ] and the specific one that measured the effect size of the individual parameter differences [ 120 , 121 , 122 ]. This study considered factor loadings (weak invariance), thresholds (strong invariance), and residuals (strict invariance), which supports hypothesis 3 (H3).…”
Section: Discussionmentioning
confidence: 99%
“…This way, there is unfavorable evidence for the measurement invariance if ΔCFI < −0.01 and ΔRMSEA ≥ 0.01 [ 104 ] or if ΔCFI < −0.002 and ΔRMSEA ≥ 0.007 [ 119 ]. The other approach is a specific one based on effect size using the comparison of specific parameters (factor loadings, thresholds, and residuals) associated with the invariance between the groups [ 120 , 121 ], taking Cohen’s indices as the reference [ 122 ]. Then, to compare the factor loadings of men and women, the coefficient q was used; magnitudes below |0.10| were expected to determine that these were equivalent between the groups.…”
Section: Methodsmentioning
confidence: 99%
“…In that sense, implementing ESEM on theoretically complex constructs could provide a more realistic point of view, and thus, an understanding of the dimensional nature of the construct [ 55 ]. Figure 1 shows the fitted models.…”
Section: Methodsmentioning
confidence: 99%
“…Adicionalmente, se implementó una rotación target oblicua (ε = .05) (18) ; la cual estima libremente aquellas cargas factoriales que pertenecen a los ítems de cada factor teórico (cargas principales), y especifica como cercanas a cero (~0) las cargas factoriales que pertenecen a los factores secundarios. Finalmente, se usaron módulos específicos para el cálculo de los índices complementarios para el análisis bifactor y el análisis de la invarianza de medición desde la perspectiva de la magnitud del efecto (27) .…”
Section: Análisis De Datosunclassified